2023
DOI: 10.48550/arxiv.2301.06522
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deciphering Faint Gyrosynchrotron Emission from Coronal Mass Ejection using Spectro-polarimetric Radio Imaging

Abstract: Measurements of the plasma parameters of coronal mass ejections (CMEs), particularly the magnetic field and non-thermal electron population entrained in the CME plasma, are crucial to understand their propagation, evolution, and geo-effectiveness. Spectral modeling of gyrosynchrotron (GS) emission from CME plasma has been regarded as one of the most promising remote sensing technique for estimating spatially resolved CME plasma parameters. Imaging the very low flux density CME GS emission in close proximity to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Mondal et al (2020) demonstrated that with high-dynamic range imaging with the MWA, it is possible to detect GS emission from slow CMEs as well and also at much higher coronal heights (∼ 4.73 R ). In another event, Kansabanik et al (2023) detected GS emission from another two slow CMEs, as shown in Figure 3. The GS radio emission from the southwestern CME is detected up to 8.5 R , the highest heliocentric distance to date.…”
Section: Spectropolarimetric Imaging Of Radio Cmesmentioning
confidence: 91%
See 3 more Smart Citations
“…Mondal et al (2020) demonstrated that with high-dynamic range imaging with the MWA, it is possible to detect GS emission from slow CMEs as well and also at much higher coronal heights (∼ 4.73 R ). In another event, Kansabanik et al (2023) detected GS emission from another two slow CMEs, as shown in Figure 3. The GS radio emission from the southwestern CME is detected up to 8.5 R , the highest heliocentric distance to date.…”
Section: Spectropolarimetric Imaging Of Radio Cmesmentioning
confidence: 91%
“…) in the presence of CME magnetic elds. Using the ground-based radio observations, these methods can be used to measure the CME-entrained magnetic elds up to ∼ 10 R (Kansabanik et al, 2023).…”
Section: Space-weather Observable At Radio Wavelengthsmentioning
confidence: 99%
See 2 more Smart Citations